La tromba-lituo di Tarquinia nel suo contesto di rinvenimento - Maria Bonghi Jovino (Aristonothos, 2010)
The contribution displays all the features regarding the trumpet-lituus found in Tarquinia by the writer herself, Maria Bonghi Jovino. Here, the lituus was found with two other bronze objects - an axe and a shield-, which are also exceptionally cast and hammered, and decorated. All these three objects were intentionally buried after having been deprived of their ‘natural’ function. The article underlines the remarkable aspects of this trumpet in comparison with figurative models and with other artifacts of the same type, in particular the Vulci lituus. This paper goes over again the extensive researches conducted during these years by the writer and other scholars on the instruments themselves, their structure, technical and organological features,  as well as the aspects emerging from the archaeological context. The historical situation implied by the archaeological evidence, connected with all the elements drawn from research, allow  the scholar to assume that the lituus,  axe and shield, were the prerogatives of a king-priest who used them during a very important ceremony. At the end of the liturgy, the objects were ritually broken and buried.